3D printing building composite material and preparation method thereof
By using carbon-absorbing gelling materials formed by calcining calcium and siliceous raw materials in 3D printing materials, combined with other components and carbonization curing processes, the problems of difficulty in absorbing carbon dioxide and high production costs of materials in the existing technology are solved, achieving High carbon sequestration and low cost 3D printing construction composite materials promote the industrial application of materials.
Patent Information
- Application Number
- CN202411884979.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing 3D printing materials are difficult to effectively absorb and fix carbon dioxide, and the production cost of materials using analytical pure chemical reagents as raw materials is high and the printing post-processing process is complex, making it difficult to achieve industrial applications.
It uses carbon-absorbing cementitious materials formed by mixing and calcining calcareous raw materials and siliceous raw materials, combined with components such as cement, silica fume, fly ash, mineral powder, cellulose ether and water-reducing agent. Through synergistic proportions and Carbonization curing process prepares 3D printed building composite materials with high carbon sequestration and low production cost.
The efficient absorption and fixed carbon dioxide of 3D printing materials have been realized. The amount of carbon solidifice is high and the production cost is low. At the same time, the finished product has high intensity. It solves the problem of high material costs in existing technology and the complex processing process, and promotes the industrial application of materials.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to a 3D printed building composite material and a preparation method thereof. Background Art
[0002] At present, most materials used for 3D printing are hydraulic cementitious materials such as ordinary cement, which are difficult to effectively absorb and fix carbon dioxide; the very few carbonization hardening materials are all prepared with analytically pure chemical reagents as raw materials. Not only is the raw material cost high, but the post-printing processing process is also complicated, making industrial production and application difficult to achieve.
[0003] The Chinese invention patent application with publication number CN109704636A discloses a carbonization hardening material for 3D printing, a preparation method and an application thereof. It uses high carbonization active calcium silicate powder as the 3D printing material. The raw material cost is relatively high and cannot be used in large-scale industrial applications. The Chinese invention patent application with publication number CN106810201A discloses a single-component ceramic 3D printing extrusion molding material and a method of using it. It uses clay as a matrix, fairy water, water glass, carboxymethyl cellulose and a water reducer as additives, and water is added to stir the material into a paste, and then 3D printing and blank post-processing are performed. This method still requires a relatively complex post-processing process after printing and molding, and post-processing processes such as sintering will also seriously affect the printing accuracy.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a 3D printed building composite material that can not only effectively absorb and fix carbon dioxide with a high carbon fixation amount, but also has a low production cost and the characteristics of high finished product strength.
[0006] The second object of the present invention is to provide a method for preparing a 3D printed building composite material, which is conducive to industrial production and application.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, a 3D printed building composite material comprises the following components by weight: 30-70 parts of carbon absorbing cementitious material, 10-40 parts of cement, 5-20 parts of silica fume, no more than 10 parts of fly ash, no more than 10 parts of mineral powder, 0.0001-0.0005 parts of cellulose ether, and 0.001-0.008 parts of water reducing agent; Wherein, the carbon absorbing gelling material comprises a carbon absorbing gelling material formed by mixing and calcining a calcium raw material and a silicon raw material; The bone-cement ratio of the 3D printing building composite material is 0.8-1.5, and the water-solid ratio is 0.1-0.2.
[0008] Furthermore, the calcium raw material includes industrial calcium raw material; The mass content of calcium oxide in the industrial calcium raw material is greater than 50%.
[0009] Further, the siliceous raw material includes industrial siliceous raw material; The mass content of silicon oxide in the industrial siliceous raw material is greater than 50%.
[0010] Furthermore, the molar ratio of the calcium raw material to the silicon raw material is (2-4):1; The fineness of the calcium raw material and the silicon raw material after mixing is less than 75 μm.
[0011] Furthermore, the calcination temperature is 1250°C-1350°C, and the calcination time is 1.5h-3h.
[0012] Further, the cement comprises P·C 42.5 cement; The aggregate used in the bone-cement ratio includes machine-made sand with a particle size less than 5 mm.
[0013] In a second aspect, a method for preparing the 3D printed building composite material as described in any one of the above items comprises the following steps: The components are mixed in proportion and then 3D printed to obtain the 3D printed building composite material.
[0014] Furthermore, the 3D printing further includes a step of carbonization curing.
[0015] Furthermore, the conditions of the carbonization curing are as follows: The CO2 concentration shall not be less than 75%; the CO2 partial pressure shall not be less than 0.02MPa.
[0016] Furthermore, the carbonization curing time is not less than 4 hours.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: The 3D printing building composite material provided by the present invention, under the coordinated cooperation of various components and their proportions, can not only effectively absorb and fix carbon dioxide, with a high carbon fixation amount, but also has a low production cost and the characteristic of high strength of the finished product; specifically, the carbon absorption gelling material has good printability, and at the same time, through the coordinated cooperation of various components and their proportions, not only the printing time can be independently regulated, but also in the later carbonization maintenance, the obtained finished product has the characteristics of high strength and high carbon fixation; in short, the present invention solves the technical problems in the prior art that 3D printing materials are difficult to absorb and fix carbon dioxide, or use analytical pure chemical reagents as raw materials, not only the production cost is high, but also the post-printing processing process is complicated, which makes it difficult to achieve industrial application.
[0018] The preparation method of the 3D printing building composite material provided by the present invention is conducive to realizing industrial production and application. DETAILED DESCRIPTION
[0019] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] According to a first aspect of the present invention, there is provided a 3D printed building composite material, comprising the following components in parts by mass: 30-70 parts of carbon absorbing cementitious material, 10-40 parts of cement, 5-20 parts of silica fume, no more than 10 parts of fly ash, no more than 10 parts of mineral powder, 0.0001-0.0005 parts of cellulose ether, and 0.001-0.008 parts of water reducing agent; In the present invention, the typical but non-limiting mass fractions of carbon absorbing cementitious materials are, for example, 30 parts, 40 parts, 50 parts, 60 parts, and 70 parts; the typical but non-limiting mass fractions of cement are, for example, 10 parts, 20 parts, 30 parts, and 40 parts; the typical but non-limiting mass fractions of silica fume are, for example, 5 parts, 10 parts, 15 parts, and 20 parts; the typical but non-limiting mass fractions of fly ash are, for example, 0.5 parts, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, and 10 parts; the typical but non-limiting mass fractions of mineral powder are, for example, 10 parts, 20 parts, 30 parts, and 40 parts; The mass fraction of the active agent is, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 parts; the typical but non-limiting mass fraction of the cellulose ether is, for example, 0.0001, 0.0002, 0.0003, 0.0004, and 0.0005 parts; the typical but non-limiting mass fraction of the water reducer is, for example, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, and 0.008 parts; In the present invention, the carbon absorbing gelling material includes a carbon absorbing gelling material formed by mixing and calcining a calcium raw material and a silicon raw material; It should be noted that the conventional hydraulic gelling material needs to be ground after calcination to prepare the printing material, while the carbon absorption gelling material formed by calcining the mixture of calcium raw material and silicon raw material in the present invention has the self-pulverization property after calcination and does not need to be ground, so the material cost is lower and the energy consumption is smaller; In the present invention, the bone-cement ratio of the 3D printed building composite material can be 0.8-1.5, and its typical but non-limiting bone-cement ratio is, for example, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, and 1.5; the water-solid ratio of the 3D printed building composite material can be 0.1-0.2, and its typical but non-limiting water-solid ratio is, for example, 0.1, 0.12, 0.14, 0.16, 0.18, and 0.2; It should be noted that the appropriate bone-cement ratio and water-to-solid ratio can ensure that the 3D printing material can fully exert its high-strength characteristics; if the bone-cement ratio is too low, the buildability of the printing material will deteriorate and the strength of the finished product will decrease; if the bone-cement ratio is too high, the rheology of the printing material will deteriorate and the shrinkage performance of the finished product will deteriorate; if the water-to-solid ratio is too low, the rheology of the printing material will deteriorate and the apparent quality of the finished product will deteriorate; if the water-to-solid ratio is too high, the buildability of the printing material will deteriorate and the strength of the finished product will decrease.
[0021] The 3D printed building composite material provided by the present invention, under the coordinated cooperation of various components and their proportions, can not only effectively absorb and fix carbon dioxide with a high carbon fixation amount, but also has a low production cost and the characteristics of high strength of the finished product; specifically, the carbon absorption cementitious material has good printability, and at the same time, through the coordinated cooperation of various components and their proportions, not only the printing time can be independently regulated, but also in the later carbonization maintenance, the obtained finished product has the characteristics of high strength and high carbon fixation.
[0022] In summary, the present invention solves the technical problems in the prior art that 3D printing materials are difficult to absorb and fix carbon dioxide, or use analytically pure chemical reagents as raw materials, which not only has high production costs but also complex post-printing processing processes, making it difficult to achieve industrial applications.
[0023] In a preferred embodiment, the calcium raw material includes but is not limited to industrial calcium raw material, and the mass content of calcium oxide in the industrial calcium raw material can be greater than 50%.
[0024] In a preferred embodiment, the siliceous raw material includes but is not limited to industrial siliceous raw material, and the mass content of silicon oxide in the industrial siliceous raw material can be greater than 50%.
[0025] The present invention adopts white carbon absorption gelling material obtained by calcining industrial-grade raw materials (industrial calcium raw materials and industrial silicon raw materials). The white carbon absorption gelling material does not need to be ground. As a 3D printing material, it is not only low in cost, but also has adjustable printing time. At the same time, the printed products have the characteristics of high strength and high carbon fixation after carbonization curing.
[0026] In a preferred embodiment, the molar ratio of the industrial calcium raw material to the industrial silicon raw material may be (2-4):1, for example, 2:1, 3:1, 4:1, but not limited thereto, which is more conducive to improving the formation effect of the carbon absorption gelling material.
[0027] In the present invention, the fineness of the mixed calcium raw material and silicon raw material can be less than 75 μm, which is more conducive to further improving the effect of calcining to form a carbon absorption gelling material.
[0028] In a preferred embodiment, the calcination temperature may be 1250°C-1350°C, and typical but non-limiting temperatures include 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C, and 1350°C; the calcination time may be 1.5h-3h, and typical but non-limiting times include 1.5h, 2h, 2.5h, and 3h. Appropriate calcination temperature and time can ensure that the calcium raw material and the silicon raw material are fully calcined to form a carbon-absorbing gelling material.
[0029] A typical method for preparing a carbon absorbing gelling material comprises the following steps: The industrial calcium raw material and the industrial silicon raw material are mixed in a molar ratio of (2-4):1, and then placed in a ball mill to mix until the fineness is less than 75µm. The resulting mixture is calcined at a temperature of 1250°C-1350°C for 1.5h-3h, and then cooled to room temperature to obtain a carbon absorption gelling material.
[0030] In the present invention, the cement used includes but is not limited to P·C 42.5 cement.
[0031] In a preferred embodiment, the aggregate used in the bone-cement ratio includes but is not limited to machine-made sand with a particle size of less than 5 mm, which can not only enhance the fluidity and plasticity of the printing material, but also improve the printing accuracy and surface quality.
[0032] According to a second aspect of the present invention, there is provided a method for preparing the 3D printed building composite material as described in any one of the above, comprising the following steps: The components are mixed in proportion and then 3D printed to obtain a 3D printed building composite material.
[0033] The preparation method of the 3D printing building composite material provided by the present invention is conducive to realizing industrial production and application.
[0034] In the present invention, a step of carbonization curing is also included after 3D printing.
[0035] In a preferred embodiment, the conditions of carbonization curing are as follows: The CO2 concentration shall not be less than 75%; the CO2 partial pressure shall not be less than 0.02MPa.
[0036] In a preferred embodiment, the carbonization curing time is not less than 4 hours.
[0037] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0038] Examples 1-4 Examples 1-4 provide a 3D printed building composite material, wherein the components and mass fractions, bone-cement ratio, and water-solid ratio are shown in Table 1.
[0039] The carbon absorbing gelling material used in Examples 1-4 is prepared by the following method: Industrial limestone and industrial high silica are dried, ground and sieved by ball milling, and mixed according to a calcium-silicon ratio of 2:1. The mixed materials are then put into a ball mill and mixed and ball milled for 0.5 hours to obtain a calcined raw material with a fineness of less than 75µm. The obtained sintered raw material is placed in an industrial sintering furnace, first heated to 900°C at a heating rate of 10°C / min, and kept warm for 30 minutes to allow the CaCO3 in the raw material to fully decompose, then heated to 1300°C at the same heating rate and kept warm for 2 hours. After the insulation is completed, it is cooled to room temperature at a cooling rate of 2°C / min to obtain the desired carbon absorption gelling material.
[0040] The solid content of the water reducing agent used in Examples 1-4 is 32%, and the water reduction rate is 30%; The aggregate used in the bone-cement ratio in Examples 1-4 is machine-made sand with a particle size of less than 5 mm.
[0041] Table 1
[0042] Example 5 This embodiment is a method for preparing the 3D printed building composite material of embodiment 1, comprising the following steps: According to the mass parts of the formula, the carbon absorption cementitious material, P·C 42.5 cement, silica fume, fly ash, mineral powder, cellulose ether, and machine-made sand weighed according to the ratio of bone to glue are fully mixed to obtain dry material; Weigh water according to the water-to-solid ratio, mix the water reducer with the water, and then place the dry material and the liquid in a cement mortar mixer and fully stir to form a mixed material, which is then 3D printed; The printed product is carbonized and cured under the conditions of 75% curing humidity, 100% CO2 concentration, and 0.02MPa CO2 partial pressure for 4 hours to obtain a 3D finished product, namely, a 3D printed building composite material.
[0043] Embodiment 6-8 Examples 6-8 are respectively methods for preparing the 3D printed building composite materials of Examples 2-4, and with reference to Example 5, 3D printed building composite materials are obtained.
[0044] Comparative Example 1 This comparative example provides a 3D printed building composite material, which is different from Example 1 in that the water-to-solid ratio in this comparative example is 0.225; The rest is the same as Example 1, and the preparation method is referred to Example 5.
[0045] Comparative Example 2 This comparative example provides a 3D printed building composite material, which is different from Example 2 in that the bone-cement ratio in this comparative example is 0.6; The rest is the same as Example 2, and the preparation method is referred to Example 5.
[0046] Comparative Example 3 This comparative example provides a 3D printed building composite material, which is different from Example 3 in that no silica fume is added in this comparative example, and the mass fraction of the added mineral powder is 15 parts; The rest is the same as Example 3, and the preparation method is referred to Example 5.
[0047] Comparative Example 4 This comparative example provides a 3D printed building composite material, which is different from Example 4 in that the printed product obtained in this comparative example is carbonized and cured under a CO2 concentration of 25%; The rest is the same as Example 4, and the preparation method is referred to Example 5.
[0048] Comparative Example 5 This comparative example provides a 3D printed building composite material, which is different from Example 1 in that the mass fraction of the carbon absorption gelling material added in this comparative example is 80 parts; The rest is the same as Example 1, and the preparation method is referred to Example 5.
[0049] Compared with Example 1, the drawback of this comparative example is that the buildability during the printing process is poor, the stacking is unstable, and ultimately the printing failure occurs.
[0050] Comparative Example 6 This comparative example provides a 3D printed building composite material, which is different from Example 1 in that the mass fraction of the carbon absorption gelling material added in this comparative example is 20 parts; The rest is the same as Example 1, and the preparation method is referred to Example 5.
[0051] Compared with Example 1, the disadvantage of this comparative example is that the apparent quality of the printed product is reduced and the carbon fixation ability is weakened.
[0052] Test example The 3D printed building composite materials obtained in Examples 1-4 and Comparative Examples 1-4 were tested, and the test results are shown in Table 2.
[0053] Test method: Refer to the "3D Printing Concrete Mixture Performance Test Method" to test the cylinder slump, fluidity and static yield stress of the concrete to determine whether it meets the printability requirements; refer to the "3D Printing Concrete Basic Mechanical Properties Test Method" to test the mechanical properties of the concrete formula.
[0054] Table 2
[0055] It can be seen that the present invention utilizes the high-carbonized hardened material obtained by calcining industrial calcium raw materials and industrial silicon raw materials as the cementitious material. The raw materials are cheap and easy to obtain, and the production cost is low. At the same time, by adjusting the types and amounts of cementitious materials, admixtures, and additives, as well as the size of the bone-cement ratio and the water-solid ratio, not only the 3D printing time can be adjusted according to actual needs, but also combined with the carbonization curing process, a finished product with high strength and high carbon fixation characteristics can be obtained; in short, the present invention not only achieves low cost and high performance of 3D printing materials, but also effectively alleviates the problems of high carbon emissions and high energy consumption in the existing cement production process.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A 3D printed building composite material, characterized in that: It includes the following components by mass: 30-70 parts of carbon absorbing cementitious material, 10-40 parts of cement, 5-20 parts of silica fume, no more than 10 parts of fly ash, no more than 10 parts of mineral powder, 0.0001-0.0005 parts of cellulose ether, and 0.001-0.008 parts of water reducing agent; Wherein, the carbon absorbing gelling material comprises a carbon absorbing gelling material formed by mixing and calcining a calcium raw material and a silicon raw material; The calcium raw material is an industrial calcium raw material; The mass content of calcium oxide in the industrial calcium raw material is greater than 50%; The siliceous raw material is an industrial siliceous raw material; The mass content of silicon oxide in the industrial siliceous raw material is greater than 50%; The molar ratio of the calcium raw material to the silicon raw material is (2-4):1; The fineness of the calcium raw material and the silicon raw material after mixing is less than 75µm; The calcination temperature is 1250°C-1350°C, and the calcination time is 1.5h-3h; The bone-cement ratio of the 3D printing building composite material is 0.8-1.5, and the water-solid ratio is 0.1-0.
2.
2. The 3D printed building composite material according to claim 1, characterized in that: The cement includes P·C 42.5 cement; The aggregate used in the bone-cement ratio includes machine-made sand with a particle size less than 5 mm.
3. A method for preparing a 3D printed building composite material according to claim 1 or 2, characterized in that: The following steps are involved: The components are mixed in proportion and then 3D printed to obtain the 3D printed building composite material.
4. The preparation method according to claim 3, characterized in that: The 3D printing also includes a step of carbonization curing.
5. The preparation method according to claim 4, characterized in that: The conditions of the carbonization curing are as follows: The CO2 concentration shall not be less than 75%; the CO2 partial pressure shall not be less than 0.02MPa.
6. The preparation method according to claim 5, characterized in that: The carbonization curing time is not less than 4 hours.
Citation Information
Patent Citations
One-component ceramic 3D printing extrusion molding material and using method thereof
CN106810201A
Carbonized hardened material for 3D printing, preparation method for carbonized hardened material and application of carbonized hardened material
CN109704636A
3D printing material based on gas driving as well as preparation method and application thereof
CN111268994A
Preparation method of gamma-C2S-based cementing material
CN111393050A